Inventory Information System Design at Kian Jaya Farma Pharmacy - Hastuti , Candra; Iman, Rizki Nur; Rahayu, Resti; Pakaja, Fachrudin (Jurnal Teknologi Informatika dan Komputer, 2025)
Information systems are developing very rapidly which is a combination of information technology and the activities of people who use it to support operations and management. In this development there have been many recent advances to help carry out work. Inventory is a system that manages data on all inventory of goods related to logistics activities carried out by a business. Inventory is often also referred to as an inventory system. Meanwhile, inventory itself is more often used to refer to inventory data. Meanwhile, an inventory information system is a software system that will assist the inventory process by implementing strict inventory administration procedures, recording from incoming goods, storage, to outgoing goods. Efficient inventory management helps pharmacies control drug purchasing costs, monitor drug expiration dates and ensure they do not run out of stock of important items. This research aims to store data and information centrally in a database to record the supply of medicines needed by patients and avoid stock outs that can disrupt health services. This system was developed using the waterfall method with Visual Studio Code, PHP and PHP My Admin software, while for system testing using the black box method to determine its functionality. The results of the research show that the inventory information system can assist in managing drug supplies, calculating drug stock, as well as preparing drug sales reports for both input and output at the Kian Jaya Farma pharmacy.